Interactive Futures: The Integration of Digital Technologies into Mathematics Education - Erdogan, Fatma (My University, 2025)
Given the abstract nature of mathematics, which often hinders student understanding, digital technologies serve to make learning more accessible and engaging. This review offers a comprehensive analysis of how digital tools are employed in mathematics education, emphasizing theoretical frameworks, application areas, and pedagogical implications. Drawing on the Technological Pedagogical Content Knowledge model and the instrumental orchestration approach, the study examines teachers’ competencies in technology integration and the instructional impact of digital tools. What is more, applications such as augmented reality, dynamic geometry software, and gamified platforms are shown to enhance students' achievement, motivation, and engagement, while mitigating mathematics anxiety. Nonetheless, factors such as limited pedagogical readiness, infrastructure deficiencies, and unequal digital literacy among teachers and students remain significant barriers. The study concludes by recommending strategies for sustainable integration, including improvements in teacher education, content development, and education policy. It urges further research into the instructional potential of emerging digital technologies.
Keywords: Mathematics education; technology integration; Digital technologies; technology-based instruction